A New Fault Location Method for Modern Distribution Network Based on System Parameters Estimation and Self-correction - Mou, Shanke; Yang, Nan; Chen, Hao; Liu, Ziqiu; Yang, Shujing (IEEE International Conference on Smart Grid and Smart Cities (Online), 2024)
The parameters of a distribution network are subject to changes due to factors such as weather conditions and load variations. The limited installation of sensing devices and data transmission delays make it difficult to obtain accurate real-time parameters of the distribution network, thereby affecting the accuracy of traditional fault location methods. To address these issues, this paper proposes a fault location method for distribution networks that dynamically adjusts the fault location model with parameter variations, based on the self-correction technology of a digital twin model of the distribution network. Additionally, a digital twin platform was developed using a digital twin server and a real-time simulation platform (RTDS), achieving synchronous operation of the physical model and the digital twin model of the distribution network in real-time. In the case study simulations, the proposed digital twin-based fault location method was validated using the digital twin platform. The results show that this method can correct distribution network parameters in real-time under various system operating conditions, significantly improving the speed and accuracy of fault location in the distribution network.